30 Great Myths about Shakespeare. - Maguire, Laurie (Wiley, 2012)
Think you know Shakespeare? Think again ... Was a real skull used in the first performance of Hamlet? Were Shakespeare's plays Elizabethan blockbusters? How much do we really know about the playwright's life? And what of his notorious relationship with his wife? Exploring and exploding 30 popular myths about the great playwright, this illuminating new book evaluates all the evidence to show how historical material-or its absence-can be interpreted and misinterpreted, and what this reveals about our own personal investment in the stories we tell.